Bispecific Antibodies and Other Non-CAR Targeted Therapies and HSCT: Decreased Toxicity for Better Transplant Outcome in Paediatric ALL? - Kállay, Krisztián Miklós; Algeri, Mattia; Buechner, Jochen; Krauss, Aviva C. (Frontiers in Pediatrics, 2022)
This review will address the place of innovative, non-chemotherapy, non-CAR-T targeted therapies in the treatment of Acute Lymphoblastic Leukemia (ALL), focusing on their use in the hematopoietic stem cell transplant (HSCT) context. The focus will be on the agent with the most experience to date, namely the bispecific T-cell engater (BiTE) blinatumomab, but references to antibody-drug conjugates (ADCs) such as inotuzumab ozogamicin and monoclonal antibodies such as daratumamab will be made as well. Specific issues to be addressed include: -The use of these agents to reduce measurable residual disease (MRD) prior to HSCT and their potential for improved transplant outcomes due to reduced toxicity compared to traditional chemotherapy salvage, as well as potentially increased toxicity with HSCT with particular agents; -the appropriate sequencing of innovative therapies, e.g., when to use BiTEs or antibodies vs CARs in the context – pre- and/or post- of HSCT; this will include also the potential for impact on response of one group of agents on the response to the other; - the role of these agents particularly in the post-HSCT relapse setting, or as maintenance to prevent relapse in this setting; -special populations in which these agents may substitute for traditional chemotherapy during induction or consolidation in patients with predisposing factors for toxicity with traditional therapy (e.g. Trisomy 21, infants), or those who develop infectious complications precluding delivery of full standard-of -care (SOC) chemotherapy during induction/consolidation (e.g. fungal infections); -the evidence we have to date regarding the potential for substitution of blinatumomab for some of the standard chemotherapy agents used pre-HSCT in patients without the above risk factors for toxicity, but with high risk disease going into transplant, in an attempt to decrease current rates of transplant related mortality as well as morbidity; -the unique toxicity profile of these agents and concerns regarding particular side effects in the HSCT context. The manuscript will include both the data we have to date regarding the above issues, ongoing studies that are trying to explore them, and suggestions for future studies to further refine our knowledge base.